The Epistemology of Ta’dib in Islamic Civilizational Discourse: Reviving and Reconstructing Contemporary Muslim Scholars’ Views - Husni, Husni; Hayden, Walter (Journal of Al-Tamaddun, 2024)
Since the end of the twentieth century, a new epistemic discourse on education has emerged. This discourse appears in tandem with the enthusiasm of the pioneers of the new age of science movement in offering brilliant ideas as an alternative to modern scientific epistemology. This study aims to provide a new epistemological construction of education synthesized from contemporary Muslim scholars’ ideas and works. This study adopts the narrative literature review method. We use this method to locate the literature on contemporary epistemology and the current educational crisis. This study has not only succeeded in making abstractions from the ideas of Muslim scholars but also in synthesizing three patterns of scholarly entity ideas: figures of new epistemological movements, with their characteristics of eclecticism, religious syncretism, monism, pantheism, exaltation of humanity, transformative, ecologically oriented, and holistic; and ideas from critical pedagogical figures; and most importantly, the standpoints of contemporary Muslim scholars. The construction of a new epistemology of education moves from monotheism as the foundation of education, restructuring the educational curriculum based on the structure of Islamic knowledge, and a vision of education that equally respects and liberates human beings.